Articles - Louis-Edmond Hamelin (Cahiers de géographie du Québec, 2005)
Usually, studies dealing with the Canadian economy hardly treat the Northwest Territories (40 000 inhabitants). Notwithstanding, per capita volume of business carried on in the NWT is among the highest in Canada. This text considers three aspects of this phenomenon. The value of production and capital amount roughly to 600 000 000 dollars per year. Of that sum, 65% comes from the South where the Government shares 50% of the total and only 3% is raised by Amerindians. The North maintains, in fact, colonial like status.The annual NWT budget exceeds $100 000 000. Most of expenses are in the social field unlike the Provinces, the NWT have no jurisdiction on the non-renewable resources. Only 10% of revenues are raised inside the territorial lands. The Federal Government must provide the necessary subsidies and share some joint programs. With respect to public finances, the NWT are as a bottomless pit. The small eskimo community of Pelly Bay (215 inhabitants) requires investments on the order of $1 500 000 and it operates with annual expenses of $250 000 for an annual value of production of $225 000. Primary and tertiary activities dominate. Local capital is insufficient for sustaining the village.Activities in the NWT are not proceeding from comprehensive planning that should be northern minded, adapted to regional needs, articulated to all sectors of economy, and elaborated in a long range perspective. Généralement, les Territoires-du-Nord-Ouest (40 000 habitants) ne sont guère considérés dans les tableaux traitant de l'économie du Canada. Pourtant, per capita, le volume total des affaires manutentionnées à l'intérieur des TNO est l'un des plus élevés de tout le pays. Nous n'étudierons que trois thèmes ceux-ci sont très rarement abordés même par ceux qui écrivent sur l'économie du Nord.L'examen de la masse générale des affaires (valeur de production et capitaux) montre un état élevé de dépendance à l'endroit de l'extérieur (qui fournit 65%), une participation gouvernementale à 50% et l'effacement de l'économie ...